2014
DOI: 10.1007/s00404-013-3131-2
|View full text |Cite
|
Sign up to set email alerts
|

The hysteroscopy and histological diagnosis and treatment value of chronic endometritis in recurrent implantation failure patients

Abstract: CE occurs frequently in RIF patients; hysteroscopy has more diagnostic and treatment value for them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
131
1
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(150 citation statements)
references
References 25 publications
12
131
1
6
Order By: Relevance
“…The relationship between CE and infertility has recently emerged as an important clinical challenge. In fact, 2.8–56.8% of infertile women, 14–67.5% of women with RIF, and 9.3–67.6% of women with recurrent pregnancy loss are diagnosed with CE . Considering these high prevalence rates, CE is a condition that must not be ignored during fertility treatment.…”
Section: Epidemiology and Clinical Featuresmentioning
confidence: 99%
“…The relationship between CE and infertility has recently emerged as an important clinical challenge. In fact, 2.8–56.8% of infertile women, 14–67.5% of women with RIF, and 9.3–67.6% of women with recurrent pregnancy loss are diagnosed with CE . Considering these high prevalence rates, CE is a condition that must not be ignored during fertility treatment.…”
Section: Epidemiology and Clinical Featuresmentioning
confidence: 99%
“…During the last decade hysteroscopy has become the tool of choice for the evaluation of the endometrial cavity including assessment of abnormal uterine bleeding (AUB), infertility, and recurrent pregnancy loss (RPL) [1][2][3]. The ever increasing value of diagnostic and operative hysteroscopy for patients with AUB serves as an appropriate tribute to Pantaleoni, who in 1869 described this procedure to look inside the uterus and could visualize an endometrial polyp [4].…”
Section: Introductionmentioning
confidence: 99%
“…In cases of CE, the peaceful co-existence between the host immunity and microorganisms breaks down, the distribution of lymphocytes involved in the implantation of embryos is altered, and ultimately, EM receptivity is reduced due to the inadequate secretion of various cytokines. Recent clinical studies in patients with RPL or RIF showed that antibiotic treatment for CE could produce dramatic changes in future pregnancy outcomes [14222425]. Our review article attempted to evaluate the benefits of hysteroscopic procedures in the diagnosis and treatment of latent CE as an addition to extant theories.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study including patients with unexplained RPL, the patients in whom hysteroscopic findings normalized after antibiotic treatment for CE, regardless of the results of endometrial cultures, showed a significantly higher incidence of successful pregnancy than the patients who did not show normalization [24]. Considering the link between hysteroscopic CE findings and poor reproductive outcomes, the difficulties involved in the pathological diagnosis of CE, and the discrepancy between pathological and hysteroscopic findings, hysteroscopic evaluation of the endometrial cavity should be considered as a regular test in clinical practice in the assessment of patients with RIF or RPL [2425]. …”
Section: Diagnosis Of Cementioning
confidence: 99%
See 1 more Smart Citation